Clinical And Toxicological Aspects Associated With Paracetamol Poisoning And Predictors Of Its Outcomes - Zyoud, Sa'ed H. A. (2011)
Paracetamol is a common source of poisoning, and early identification of patients with more severe poisoning is the key to improving outcomes. Many aspects of paracetamol toxicity and treatment remain poorly understood. To improve knowledge about paracetamol poisoning, the current 5-year, hospital-based study was carried out with the following primary objectives (1) to determine the pattern of paracetamol poisoning among patients who were admitted to Hospital Pulau Pinang (HPP); and (2) to identify indicators of poor prognosis at first hospital presentation for improving clinical care and determining intervention targets for prevention, early detection, diagnosis and treatment. This is an observational retrospective cohort study of hospital admissions for acute paracetamol poisoning between 1 January 2004 and 31 December 2008. Overall, 305 patients met the inclusion criteria. Gastrointestinal (GI) manifestations were common in patients who reported ingestion of ≥ 8 g of paracetamol, and whose latency was longer than 8 hours; and both of these factors were identified as strong independent predictors of the presence of GI manifestations, especially nausea/vomiting. The presence of GI symptoms was a significant marker of poor outcomes and increased hospital stays. Additionally, hypokalaemia is highly associated with paracetamol poisoning. Specific clinical characteristics upon first presentation to the hospital, such as vomiting, psychiatric illness, and reported paracetamol dose ingested, can be used to identify patients at increased risk for hypokalaemia. Importantly, long hospital stays were significantly less frequent when IV-NAC therapy was administered within 8 hours of paracetamol ingestion (p = 0.006).